Testing the Reference-Dependent Model: A Laboratory Search Experiment - Takahiro Miura; Keigo Inukai; Masaru Sasaki (Institute of Labor Economics (IZA), 2019)
Our paper conducts laboratory experiments with the sequential search model to test whether participants engage in search activities in line with theoretical predictions derived from the expected utility model or the reference-dependent model, without assuming any specific formulation rule for a reference point. Our experimental results showed that the participants' search behavior did not align with the reference-dependent model. In addition, the correlation between individual preferences and search behavior reinforced our experimental results; that is, loss aversions were not significantly correlated with search behavior.
Keywords: D81; D83; 330; sequential search; loss aversion; risk preference